Current Themes in Theoretical Biology
VIII, 310 p.
Keywords: The present volume originated in 2001 when we, together with our publishing editors at (then) Kluwer Academic Publishers, realized that the th following year the 50 volume of our journal Acta Biotheoretica would see the light. We felt that this milestone should not pass unnoticed and that the appropriate way to mark it would be the publication of a special volume of papers on theoretical biology. While editing this book during 2003 and early 2004, we realized that another milestone was not far off: in 2005 it will be 70 years ago that the journal was founded. We hope that the book lying before you will serve well to mark both events. The papers collected here have been written on invitation by representatives of the theoretical biology community in The Netherlands. They are intended to reflect the entire spectrum of topics on which Acta Biotheoretica publishes, ranging from philosophy of biology on one end to mathematical biology on the other. All chapters (except our own introductory one) have been peer reviewed according to the standards that are maintained with respect to regular submissions to Acta Biotheoretica.